2016
DOI: 10.4172/2329-6771.1000178
|View full text |Cite
|
Sign up to set email alerts
|

A Liver Index and its Relationship to Indices of HCC Aggressiveness

Abstract: A Hepatocellular (HCC) Aggressiveness Index was recently constructed, consisting of the sum of the scores for the 4 clinical parameters of maximum tumor size, multifocality, presence of portal vein thrombus and blood alphafetoprotein levels. It was observed that there was an association with several liver function tests. We have now formed a Liver Index from the 4 liver parameters with the highest hazard ratios with respect to HCC aggressiveness, namely: blood total bilirubin, gamma glutamyl transpeptidase (GG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
3
36
0
2
Order By: Relevance
“…However, the decrease in cell growth was not associated with significant induction of apoptosis or autophagy. This represents another example of HCC biology in relation to microenvironmental liver factors [28] . Whether the albumin-mediated growth decrease is a result of an inhibitory action on AFP or a direct effect on the cell proliferation machinery/signaling has yet to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…However, the decrease in cell growth was not associated with significant induction of apoptosis or autophagy. This represents another example of HCC biology in relation to microenvironmental liver factors [28] . Whether the albumin-mediated growth decrease is a result of an inhibitory action on AFP or a direct effect on the cell proliferation machinery/signaling has yet to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, albumin, as part of the ALBI grading system, has been shown to be a quantitative, useful and prognostic indicator of liver dysfunction in HCC patients (21)(22)(23)(24)(25). Albumin has previously been reported to have direct HCC growth inhibitory properties in vitro (26,27), and there is also suggestive clinical evidence for an inhibitory effect on HCC in patients (30)(31)(32). Several studies have also shown a decrease in albumin levels in human HCC cells compared with the non-HCC liver (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…II) renders this explanation less likely. However, there is recent evidence suggesting an association between HCC growth and poorer liver function, except for albumin, which seems to be protective (27,(30)(31)(32). The mechanisms by which albumin might protect against HCC growth or damage are not yet clear, although there is some experimental evidence that albumin might directly suppress HCC growth (26,27), leading us to consider the possibility that in addition to its reflection of liver synthetic function and systemic inflammation, it might also have a direct tumor growth-modulating function in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary evidence has shown reduced HCC recurrence rates after resection and reduced death from all causes in HCC patients. [39][40][41][42][43][44] As the new therapies become incorporated into many aspects of HCC treatment, it is likely that they will enhance survival rates for HCC ablation, resection, and transplant.…”
Section: Effective New Antiviral Therapies: Are They Now Part Of Hepamentioning
confidence: 99%